A recurrent lung abscess caused by delayed diagnosis of unique co-infection with Abiotrophia defectiva. (6th November 2020) - Onorati, Ilaria; Guiraudet, Patrice; Billard-Pomares, Typhaine; Martinod, Emmanuel
Abstract: We report the case of a lung abscess due to Prevotella baroniae with a co-infection by Abiotrophia defective, which is a 'nutritionally variant streptococci' (NVS), in a 48-year-old patient. The delayed diagnosis of this co-infection led to multiple failures of medical treatment and need for surgery. Pathogenicity of these bacteria is well known, particularly in endocarditis, but not in lung infection. In pulmonary abscesses, co-infection with NVS is difficult to detect. It may explain some medical treatment failures. This case highlights the importance to systematically search for and consider NVS in such clinical contexts. Abstract : Lung abscesses are generally caused by anaerobic bacteria or streptococci.